2013
DOI: 10.1158/1078-0432.ccr-12-1281
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Identifies Tyrosine Kinase c-Met as a Targetable Mediator of Antiangiogenic Therapy Resistance

Abstract: Purpose To identify mediators of glioblastoma anti-angiogenic therapy resistance and target these mediators in xenografts. Experimental Design We performed microarray analysis comparing bevacizumab-resistant glioblastomas (BRGs) to pre-treatment tumors from the same patients. We established novel xenograft models of anti-angiogenic therapy resistance to target candidate resistance mediator(s). Results BRG microarray analysis revealed upregulation versus pre-treatment of receptor tyrosine kinase c-Met, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
199
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(209 citation statements)
references
References 40 publications
6
199
0
4
Order By: Relevance
“…The HGF-mediated change in the expression of these factors promotes tumor angiogenesis. These insights might explain the action of HGF/MET signaling as an endogenous resistance factor for VEGFR-targeted inhibitors (40,41). Furthermore, HGF/MET signaling activity is greater under hypoxic conditions after VEGFR-targeted inhibitors treatment than under normoxia, and hypoxiainduced HGF/MET signaling activity may reinforce tumor progression and metastasis (42).…”
Section: Discussionmentioning
confidence: 99%
“…The HGF-mediated change in the expression of these factors promotes tumor angiogenesis. These insights might explain the action of HGF/MET signaling as an endogenous resistance factor for VEGFR-targeted inhibitors (40,41). Furthermore, HGF/MET signaling activity is greater under hypoxic conditions after VEGFR-targeted inhibitors treatment than under normoxia, and hypoxiainduced HGF/MET signaling activity may reinforce tumor progression and metastasis (42).…”
Section: Discussionmentioning
confidence: 99%
“…78,79 Therefore, targeting this factor in combination with antiangiogenic therapy might be effective in order to overcome resistance, and results from clinical trials are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…In glioblastoma multiforme models, Jahangiri and colleagues conducted gene expression studies suggesting that in bevacizumab-resistant tumors, MET is one of the most overexpressed genes and that genetic ablation could reverse resistance and reduce tumor cell invasion and tumor cell survival (55). Other studies suggested that dual VEGFR and MET blockade reduces metastasis and improves survival in several preclinical models (56).…”
Section: Vegf Pathway Targetingmentioning
confidence: 99%